Influence of Recycling Frequency on Mechanical and Physical Properties of Kenaf Fiber Reinforced Polyoxymethylene Composite - Dan-Mallam, Y. (Taylor and Francis Inc., 2016)
The main objective of this research is to investigate the effect of compression cycles and hybridization on mechanical and physical properties of kenaf fiber reinforced POM composite. In this study, kenaf, and polyethylene terephthalate (PET) fiber were used as reinforcements due to their excellent mechanical properties and resistance to thermal degradation during recycling process. The matrix used was polyoxymethylene (POM) copolymer due to its hydrophobic characteristics and good mechanical properties. In this investigation, two formulations namely POM/kenaf, and POM/kenaf/PET hybrid composite were carefully studied. The results of the investigation revealed that the tensile strength of both POM/kenaf, and POM/kenaf/PET after first recycling process dropped by approximately 83 and 67, respectively. The tensile strength remained consistent after second and third compression cycle. The flexural strength of both composites also dropped by nearly 50 and 53, but remained consistent after second and third compression cycle. However, the composite resistance to water absorption significantly increased due to less voids and micro-cracks observed after recycling process. The results obtained have shown that the recycled composites retained their mechanical properties after the last two compression cycles. Â© 2016 Taylor & Francis.